Human corneal endothelial cells from older donors can be cultured and passaged on cell‐derived extracellular matrix. Issue 4 (10th September 2020) - Parekh, Mohit; Ramos, Tiago; O'Sullivan, Finbarr; Meleady, Paula; Ferrari, Stefano; Ponzin, Diego; Ahmad, Sajjad
Abstract: Purpose: To investigate the effect of culturing human corneal endothelial cells (HCEnCs) from older donors on extracellular matrix (ECM) derived from human corneal endothelial cell line (HCEC‐12). Methods: HCEC‐12 cells were cultured on lab‐tek chamber slides for 9 days. Upon confluence, the cells were ruptured using ammonium hydroxide leaving the released ECM on the slide surface which was visualized using scanning electron microscope (SEM). HCEnCs from old aged donor tissues ( n  = 40) were isolated and cultured on either fibronectin‐collagen (FNC) or HCEC‐12 ECM at passage (P) 0. At subsequent passages (P1 and P2), cells were sub‐cultured on FNC and ECM separately. Live/dead analysis and tight junction using ZO‐1 staining were used to record percentage viability and morphological changes. The protein composition of HCEC‐12 ECM was then analysed using liquid chromatography–mass spectrometry. Results: SEM images showed long fibrillar‐like structures and a fully laid ECM upon confluence. HCEnCs cultured from older donor tissues on this ECM showed significantly better proliferation and morphometric characteristics at subsequent passages. Out of 1307 proteins found from the HCEC‐12 derived ECM, 93 proteins were evaluated to be matrix oriented out of which 20 proteins were exclusively found to be corneal endothelial specific. Conclusions: ECM derived from HCEC‐12 retains protein and growth factors that stimulate the growth of HCEnCs. As the current clinical trials are from younger donors that are not available routinely for cell culture, HCEnCs from older donors can be cultured on whole ECM and passaged successfully.